2021
DOI: 10.3390/biom12010021
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Related Factors in Cardiovascular Complications Associated to COVID-19

Abstract: Coronavirus disease 2019 (COVID-19), the pandemic infection caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), presents with an extremely heterogeneous spectrum of symptoms and signs. The clinical manifestations seem to be correlated with disease severity. COVID-19 susceptibility and mortality show a significant sex imbalance, with men being more prone to infection and showing a higher rate of hospitalization and mortality compared to women. Such variability can be ascribed to both sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 153 publications
0
10
0
2
Order By: Relevance
“…A predominância do sexo feminino na amostra do presente estudo corrobora com achados da pesquisa realizada por Jimeno-Almazán, et al ( 2022) que, assim como esta, aborda possíveis tratamentos para pacientes com sequelas remanescentes da infecção por Sars-Cov-2, apesar de levantamentos epidemiológicos evidenciarem que a maioria dos indivíduos acometidos pela Covid-19 são homens (Megiorni, et al, 2021;Gao, et al, 2021). Segundo Megiorni, et al (2021), uma provável explicação para esse paradoxo é o fato de que sexo e gênero são conceitos diferentes, visto que o sexo biológico compreende o conjunto de características anatômicas e fisiológicas determinantes na resposta imunológica perante a infecção.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…A predominância do sexo feminino na amostra do presente estudo corrobora com achados da pesquisa realizada por Jimeno-Almazán, et al ( 2022) que, assim como esta, aborda possíveis tratamentos para pacientes com sequelas remanescentes da infecção por Sars-Cov-2, apesar de levantamentos epidemiológicos evidenciarem que a maioria dos indivíduos acometidos pela Covid-19 são homens (Megiorni, et al, 2021;Gao, et al, 2021). Segundo Megiorni, et al (2021), uma provável explicação para esse paradoxo é o fato de que sexo e gênero são conceitos diferentes, visto que o sexo biológico compreende o conjunto de características anatômicas e fisiológicas determinantes na resposta imunológica perante a infecção.…”
Section: Resultsunclassified
“…Em contrapartida, o gênero abrange comportamentos construídos em meio ao contexto social no qual o indivíduo está inserido, influenciando assim na forma como ele se comporta durante o processo de adoecimento. Diante disso, pode-se observar que mulheres geralmente são mais atentas ao seu próprio estado de saúde e têm o hábito de buscar atendimento para solucionar o distúrbio causador dos sintomas que estejam apresentando (Megiorni, et al, 2021;Aksoyalp & Nemutlu-Samur, 2021).…”
Section: Resultsunclassified
“…The inclination in reporting adverse effects of the vaccination, being a finer aspect in the fairer gender, most trials also showed that the adverse effects of the vaccine were seen more in women than the men. [3] www.ijcdw.org…”
Section: Sex-related Disparities Existed Even For Covid-19 Vaccinesmentioning
confidence: 99%
“…Furthermore, it is unknown whether the CMR changes seen in older patients are preexisting rather than COVID-19 related. Similarly, the relationship between male sex and CMR evidence of injury is unclear [27,32,35,45,46]. In a pooled meta-analysis of 4 studies, Zou et al [43] found no statistical significance between male sex to the appearance of cardiac injury.…”
Section: Biomarkers and Risk Factors Of Cardiac Involvementmentioning
confidence: 99%